1997
DOI: 10.1021/ja961867t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Photoinduced Electron-Transfer Reactions within Sol-Gel Silica Glass Doped with Zinc Cytochrome c. Study of Electrostatic Effects in Confined Liquids

Abstract: Silica hydrogel (glass) was doped with native (iron-containing) cytochrome c and with its zinc derivative. Ultraviolet−visible, circular dichroism, and resonance Raman spectra of both proteins and the lifetime of the triplet state of the zinc protein show that encapsulation in the sol-gel glass only slightly perturbs the polypeptide backbone and does not detectably perturb the heme group. Because thermal (ground-state) redox reactions of the encapsulated native cytochrome c are very slow, we take advantage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(133 citation statements)
references
References 73 publications
7
124
2
Order By: Relevance
“…It is known that ormosils can provide silica structures with different degrees of hydrophobicity and the associated change in the pore polarity may favor the electron transfer with the electrode [52][53][54] . So, at this point, the chemical modification of the silica is studied in order to obtain structures able to modulate the electrostatic interactions between the silica walls and cyt c. was assessed by contact angle measurement (see Table S1 in Supporting Information).…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ormosils can provide silica structures with different degrees of hydrophobicity and the associated change in the pore polarity may favor the electron transfer with the electrode [52][53][54] . So, at this point, the chemical modification of the silica is studied in order to obtain structures able to modulate the electrostatic interactions between the silica walls and cyt c. was assessed by contact angle measurement (see Table S1 in Supporting Information).…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
“…Indeed, the silica hydrogel is often considered as a two-phase system consisting in a porous solid and a trapped aqueous phase 54 . We have found that the results obtained This behavior may be related with the structural characteristics of ormosils.…”
Section: Preparation Of Electrodesmentioning
confidence: 99%
“…It has been noted that the surface of the protein could also interact with or adsorb to the hydrophilic silica pore walls through electrostatic or hydrogen bonding interactions. 3,[23][24][25][26][27][28] Fluorescence anisotropy studies have demonstrated that proteins in sol-gel pores experience dramatically hindered rates of rotation due to protein adsorption to the pore walls. 23,29,30 Alternatively, the pore dimensions could influence the protein structural stability by affecting the dynamics of the surrounding solvent, which is intimately coupled to the dynamics of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Charged molecules can be partially excluded from the pore interior at low ionic strengths such as those used in these experiments. 33 The quencher plots were constructed assuming that the concentration of enzyme cofactor in the pores was equal to the concentration in bulk. It is likely that the negatively charged enzyme cofactor may not fully penetrate the sol-gel pores resulting in a lower concentration than assumed.…”
Section: Emission Spectra Of Thionine-doped Gelsmentioning
confidence: 99%